If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1(2x + 2) + -8 = -5 Reorder the terms: -1(2 + 2x) + -8 = -5 (2 * -1 + 2x * -1) + -8 = -5 (-2 + -2x) + -8 = -5 Reorder the terms: -2 + -8 + -2x = -5 Combine like terms: -2 + -8 = -10 -10 + -2x = -5 Solving -10 + -2x = -5 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '10' to each side of the equation. -10 + 10 + -2x = -5 + 10 Combine like terms: -10 + 10 = 0 0 + -2x = -5 + 10 -2x = -5 + 10 Combine like terms: -5 + 10 = 5 -2x = 5 Divide each side by '-2'. x = -2.5 Simplifying x = -2.5
| -n+15+4n+15=-3 | | -8=1.3-2.1 | | 2-(k-3)=4 | | 5x+7=67-7x | | 6.5+5y=9 | | -7-14=-w | | 2x+2-8=-5 | | -34+16=-5x+14x | | F(x)=6x^3-7x^2+2x+8 | | 1.3-2.1=-8 | | 1-(k+2)=8 | | 6[10s]= | | g(x)=-x^2-16 | | 2.16(3.74x-8.60)=1759 | | -(x+3)+9=13 | | 3-3=16x+9x | | z=4+y | | X^2+9=-55 | | x+3+9=13 | | x+3.5x+4.25x= | | 3y+1=14y-6 | | 5/x-2=9/3x-6 | | -4=x-4+2x | | 6(x-2)=10 | | -11+15+4(-11)+15=-3 | | -(x+9)+1=14 | | 2/7k-1/14k=-3 | | -42=5x | | x+9+1=14 | | 45=3x+7x+5 | | a=rn+r | | -x-4-2=31 |